Spastic cerebral palsy: a comprehensive study of bibliometrics, traditional chinese medicine symptoms analysis, and clinical intervention with acupuncture and tuina - Wang, Xing (2024)
This research adopts an interdisciplinary approach. The first one is to summarize knowledge structure to understand the hotspots, trend, and frontier of research on spastic CP. The second one is to analyze the TCM symptom in children with spastic CP. The third one is to observe the clinical effect of acupuncture and tuina on spastic cerebral palsy. Its aim is to construct a comprehensive knowledge framework dedicated to investigating spastic cerebral palsy, with the goal of laying both theoretical groundwork and practical foundations for clinical interventions. In this study, data were gathered from 3988 publications on spastic CP retrieved from the Web of Science Core Collection (WoSCC) database spanning from January 1, 2000, to November 30, 2022. Analysis was conducted using tools such as WoSCC literature analysis wire, VOSviewer 1.6.18, CiteSpace 6.1.R4, and an online analysis platform for bibliometrics. Information from medical records of 231 eligible spastic CP cases was extracted, transformed, and analyzed. The analysis focused on general information and TCM symptoms associated with the condition. Cluster analysis and association rule analysis were employed to identify TCM core symptoms and patterns of syndrome correlations among children diagnosed with spastic CP. Treatment involved acupuncture and tuina (AT) for 83 patients and conventional rehabilitation for 85 patients, administered over a 12-week period according to the research protocol. Pre- and post-treatment assessments included the Modified Ashworth muscle tension scale (MAS), Gross Motor Function Measure (GMFM-D and GMFM-E), 6-minute walking distance measurement (6MWD), and Modified Children's Functional Independence Rating Scale (WeeFIM). The results of the study revealed key bibliometric trends over the past two decades in spastic CP, highlighting productive countries, institutions, authors, and leading journals in the field. Noteworthy keywords and clusters included Spastic cerebral palsy, Reliability, and Gross motor function, with burst detection indicating hotspots such as management, controlled trials, and definition. The results provide potentially new directions in the study of spastic CP. TCM symptoms analysis showed the core symptoms among patients included motor dysfunction, impaired speech, delayed development, limb stiffness, and various tongue and pulse characteristics. Spastic CP should be classified as liver exuberant and spleen weakness of syndrome in TCM. After 12 weeks of treatment, both groups exhibited significant improvements in MAS scores (p<0.01), indicating reduced muscle tension, as well as increased scores in GMFM-D, GMFM-E, 6MWD, and WeeFIM (p<0.01 for all indicators), indicating enhanced gross motor function and functional independence. The AT group showed significantly superior outcomes compared to the control group (p<0.01 in all indicators). Furthermore, an inverse correlation was observed between children's age and treatment efficacy (r= -0.496, p<0.01 in AT group; r=-0.540, p<0.01 in control group), underscoring the importance of early intervention in CP management.